Evaluating the Potentials of Individual Lending Instructions (in Housing Fund Law) to Support Housing Finance Policies in Iraq. - Alanizi , Arshad; M.N. Alsayed, Muna (Journal of Planner and Development, 2022)
Iraqi economy has grown rapidly. Iraqi citizen, therefore, should be very much involved with the comprehensive development after his long patience. Such development should begin with him and his family to get the housing commodity, which is indeed not a cheap one.                                                             In this regard, the Iraqi legislator drew attention to the necessity of issuing housing finance legislation, and thus Law No. 32 of 2011 was enacted (the Iraqi Housing Fund Law), and instructions were issued by the Ministry of Construction and Housing (MoCH) for the purpose of facilitating the implementation of this law, based on Article 20 of the same law.                           Because of the close connection between housing finance and architecture as one of its branches in the field of housing, and after we presented another extensive research to discuss the problems contained in Housing Fund Law No. (32), this research comes to discuss the regulation and instructions (of the law itself) to help MoCH to avoid those problems and to solve them. The scope of discussions of this research is limited for the individual lending instructions.     The research also discusses some of the interpretations of the fund's           administrators regarding the law to develop them to serve our country and ourcitizens.